2009
DOI: 10.1287/moor.1090.0398
|View full text |Cite
|
Sign up to set email alerts
|

Refined MDP-Based Branch-and-Fix Algorithm for the Hamiltonian Cycle Problem

Abstract: We consider the famous Hamiltonian cycle problem (HCP) embedded in a Markov decision process (MDP). More specifically, we consider the HCP as an optimisation problem over the space of occupation measures induced by the MDP's stationary policies. In recent years, this approach to the HCP has led to a number of alternative formulations and algorithmic approaches. In this paper, we focus on a specific embedding, because of the work of Feinberg. We present a “branch-and-fix” type algorithm that solves the HCP. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Recently, Ejov et al (2008b) proposed a branch-and-bound-type algorithm for the HCP by adapting linear constraints (5)-(7). The new hybrid algorithm explained in Sect.…”
Section: Hamiltonian Cycles Through Controlled Markov Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ejov et al (2008b) proposed a branch-and-bound-type algorithm for the HCP by adapting linear constraints (5)-(7). The new hybrid algorithm explained in Sect.…”
Section: Hamiltonian Cycles Through Controlled Markov Chainsmentioning
confidence: 99%
“…Theorem 2.1 demonstrates that a convex subset of the usual "discounted frequency" polyhedral domain defined by constraints (5) and (7) reflects some properties of Hamiltonian policies and can be used as a basis of an algorithm that searches for a Hamiltonian cycle (e.g., see Feinberg 2000;Ejov et al 2008b). However, it can be argued that the polytope defined by (5), (6) and (7) has two deficiencies:…”
Section: H β -Refined Polyhedral Domainmentioning
confidence: 99%
“…Most of the later developments are recapped in monographs by Kallenberg [35], Borkar [6], Piunovskiy [42], Altman [1], and Hernández-Lerma and Lasserre [32], and in surveys by Piunovskiy [43] and Borkar [7]. It has various applications including to the Hamiltonian cycle problem; see Feinberg [21], Filar [28, § §3.3, 3.4], and Ejov et al [15]. The convex-analytic approach is also applicable to average rewards per unit time with expected state-action frequencies playing the role of occupancy measures (Derman [12], Kallenberg [35], Borkar [6], Piunovskiy [42], Altman [1]).…”
mentioning
confidence: 99%
“…Markov decision processes are applicable to a wide range of optimization problems. The model introduced in Filar and Krass [15] instigated a new line of research, which has attracted growing attention (see, for example, [4,7,8,10,9,11,14,16,20]).…”
Section: Introductionmentioning
confidence: 99%
“…Feinberg showed that if the graph G is Hamiltonian, the polytope F β (G) has an extreme point, called a Hamiltonian extreme point, for each of its Hamiltonian cycles. Subsequently, Ejov et al [10] described some geometric properties of F β (G) and Eshragh et al [13] transformed F β (G) to a polytope H β (G) to improve algorithmic efficiency. In 2011, Eshragh and Filar [12] partitioned all extreme points of H β (G) into five types, consisting of Hamiltonian extreme points and non-Hamiltonian extreme points of types 1, 2, 3 and 4.…”
Section: Introductionmentioning
confidence: 99%